Analisis Preferensi Konsumen Terhadap Keputusan Pembelian Buah Pisang di Pasar Tradisional Kota Kisaran - Marpaung, Desi Wulandari; Mukson; Ekowati, Titik (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2024)
Fruit is an agricultural product with high economic value because its good for health. Bananas (Musa paradisiaca) is the fruit most consumed by Indonesian people. Many types of banana in the market make consumers' choices more numerous and diverse. Consumers consider their preferences for different products when buying a product. This study aims to identify the characteristics of banana consumers, analyze consumer preferences, and examine the most considered attributes of bananas. The research was conducted at two traditional market locations in Kisaran City, with 60 respondents selected using accidental sampling. Data were analyzed using descriptive analysis to describe consumer characteristics, and conjoint analysis to analyze consumer preferences and the most considered attributes. The results showed that the majority of banana consumers were women, aged 20-29 years, with a bachelor's education level, four family members, and an income of > IDR 2,000,000 – IDR 3,000,000. The majority of consumers bought barangans compared to other types of bananas, and consumer preferences included bananas with a slightly sweet taste, yellow skin color, a large number of fruits per comb (≥ 14 fruits), and a price > IDR 12,000. The most considered attribute of bananas by consumers is the number of pieces per comb, with an importance value of 34.103%.